2000
DOI: 10.1016/s0965-1748(00)00095-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cysteine and aspartyl proteinases in the alfalfa weevil midgut with biochemical and plant-derived proteinase inhibitors

Abstract: "Inhibition of cysteine and aspartyl proteinases in the alfalfa weevil midgut with biochemical and plant-derived proteinase inhibitors" (2000). AbstractProteolytic activities in alfalfa weevil (Hypera postica) larval midguts have been characterized. Effects of pH, thiol activators, low-molecular weight inhibitors, and proteinase inhibitors (PIs) on general substrate hydrolysis by midgut extracts were determined. Hemoglobinolytic activity was highest in the acidic to mildly acidic pH range, but was maximal at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Genes encoding digestive enzyme inhibitors have been incorporated into plants with differing results (Oppert 2000;Oppert et al 2000). Considerate biochemical characterization of the enzymes active in the midgut of the target pests is the primary step in designing inhibitor-transgenic crops (Oppert 2000;Oppert et al 2000;Wilhite et al 2000).…”
mentioning
confidence: 99%
“…Genes encoding digestive enzyme inhibitors have been incorporated into plants with differing results (Oppert 2000;Oppert et al 2000). Considerate biochemical characterization of the enzymes active in the midgut of the target pests is the primary step in designing inhibitor-transgenic crops (Oppert 2000;Oppert et al 2000;Wilhite et al 2000).…”
mentioning
confidence: 99%
“…Protein digestion is provided by both serine and cysteine proteases in the weevils B. coerulescens (Bonadé-Bottino et al, 1999) and C. assimilis (Girard et al, 1998). It has been reported that the alfalfa weevil, Hypera postica (Elden, 1995;Wilhite et al, 2000), O. sulcatus (Michaud et al, 1995), and A. grandis (Murdock et al, 1987) have slightly acidic midguts and cysteine proteases provide the major midgut endoproteolytic activity. Nevertheless, aspartic and/or serine proteases have been identified in some of these species (Purcell et al, 1992;Wilhite et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1947, it has been observed that PIs from soybean were able to inhibit the growth of insect-pests larvae, including the coleoptera Tribolium confusum (HAQ et al, 2004;LYSON, 2002;MICKEL e STANDISH, 1947). Later, in vitro and in vivo bioassays demonstrated that protease inhibitors were also active against other insect species, such as Anagasta kuehniella, Hypera postica and Anthonomus grandis (FRANCO et al, 2003;MACEDO et al, 2003;WILHITE et al, 2000). Hence, as there is no evidence that proteinase inhibitors have toxic or deleterious effects on mammals, they constitute a significant alternative for the development of transgenic crops resistant to insect-pests and nematodes.…”
Section: Digestive Enzyme Inhibitorsmentioning
confidence: 99%